AGLOMERACIÓN ECONÓMICA Y PROBLEMAS URBANOS EN EL CENTRO DE HERMOSILLO, SONORA. - Garza, Daniel Fanco (UNIVERSIDAD DE SONORA, 2018)
City centers are fundamental pieces of Mexican cities and, in many cases, they represent their origins and act as spaces of diversity and economic activity, concentrating an important commercial and services variety, to which thousands of the cities inhabitants have access daily and/or regularly. While these spaces are important and serve as a reference in the cities, the same concentration or economic and commercial agglomeration entails a series of complexities and problems, given the big activity that they develop, and in which a vast and diverse amount of actors participate, making the dynamics of these city centers an interesting system composed by several interconnected parts, whose links create additional information, not always easily observable. In this essay, this system of complexities and particularities are analyzed, as well as the actors involved, presenting, at the same time, the problems of urban development that this economic space of the city of Hermosillo concentrates.